Obesity and anemia in pregnant women at low and high altitude - Olavegoya, Paola (2019)
Objective. To demonstrate if pregestational obesity in populations living at low and at high altitudes was associated with hemoglobin (Hb) reduction and if changes are observed in each of the trimesters of pregnancy. Methods. We used a database containing information from 1’712,639 pregnant women belonging to each of the 24 departments of Peru obtained during the period 2012 to 2017. Pre-pregnancy Weight and height were determined, and BMI was calculated and expressed as weight in kilograms divided by the square of height in meters. Data about weight gain during pregnancy was also recorded. Hemoglobin was measured using hemocue. Data are presented as uncorrected hemoglobin concentration (g/dL) as well as corrected hemoglobin concentration (g/dL) after adjusting its value by altitude as recommended by World Health Organization. Data were analyzed using bivariate and multivariate analysis. P<0,05 was considered as significant. Results. Increase of BMI category increased the hemoglobin concentration (corrected or uncorrected) (p <0,0001) whereas, the weight gain from pregnancy is lowered in a dose-response fashion as BMI category increased (P <0,0001). Significant differences were found in age (years) and BMI (Kg/m2) between all groups regarding trimester (p <0,0001). Women with overweight and obesity does not increase weight at first trimester of pregnancy. Obesity was associated with low weight gain at second and third trimester of pregnancy. Higher pregnancy weight gain was correlated with lower hemoglobin concentration (R² = 0,963; p<0,0001). Conclusions. It is necessary to measure the plasma volume of pregnant women, as this would avoid misinterpretations of hemoglobin concentration in overweight and obese pregnant women.